(untitled) (Research, Society and Development, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is a lung disease, often associated with smoking. COPD patients have persistent, including urinary incontinence. Therefore, a research has the general objective of knowing the physiological mechanism of urinary incontinence associated with the pharmacological treatment of COPD. As a methodological process, this study is an integrative review that included randomized clinical trials, quasi-experimental intervention studies, cohort and case-control. The selection of studies was carried out in the databases PubMed, SciELO, Science Direct and BVS (Virtual Health Library), published between 2010 and July 2020, in Portuguese and English. Pharmacological classes SABA, LABA, SAMA, LAMA, ICS and iPDE4 were considered to investigate adverse effects and check for the presence of urinary symptoms caused by these drugs. In the results and discussion, 113 articles were identified with the investigated descriptors. After the article selection process, 14 studies resulted: PubMED (13); and Science Direct (1). The pharmacological class related to urinary incontinence identified in this study was that of anticholinergics / antimuscarinics. From this perspective, it can be considered that Urinary Incontinence has a low relationship with the adverse effects of drugs for the treatment of Chronic Obstructive Pulmonary Disease (COPD). However, as urinary incontinence is not considered a life-threatening problem, it is possible that it has not been included among the adverse events to be explored.